2018
DOI: 10.3926/ic.1106
|View full text |Cite
|
Sign up to set email alerts
|

The predictability of financial, accounting‐based, and industrial factors on the success of newly incorporated Spanish firms

Abstract: Purpose: The purpose of this paper is to identify the impacts and predictability of financial, accounting-based, and industrial factors (as well as corporate venturing) on survival-based success of newly incorporated firms in Spain.Design/methodology: Logistic regression is used for comparing the differences of factors in the prediction of future success after different time periods since the studying years (age 1, age 2, and age 3 respectively) in manufacturing and distributive sectors.Findings: Differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(99 reference statements)
0
2
0
2
Order By: Relevance
“…On the other hand, Collard-Wexler (2014) showed that barriers to entry hurt market performance, as did Lee and Yang (2016). Tong and Saladrigues (2018) showed a similar relationship with the probability of business survival in Spain. D. McGowan (2014) found that a higher level of barriers to entry helps avoid creative destruction processes; in other words, they encourage inefficient companies to remain in the market.…”
Section: Industry Characteristicsmentioning
confidence: 79%
“…On the other hand, Collard-Wexler (2014) showed that barriers to entry hurt market performance, as did Lee and Yang (2016). Tong and Saladrigues (2018) showed a similar relationship with the probability of business survival in Spain. D. McGowan (2014) found that a higher level of barriers to entry helps avoid creative destruction processes; in other words, they encourage inefficient companies to remain in the market.…”
Section: Industry Characteristicsmentioning
confidence: 79%
“…Several similar studies have been carried out in many countries, but, in general, they deal with the industrial and commercial sectors. In any case, they constitute a starting point as long as they identify variables with an impact on profitability, such as indebtedness, number of employees, size of assets or level of activity, which will be used in this case (17)(18)(19)(20)(21)(22) .…”
Section: Indicators Of Corporate Profitabilitymentioning
confidence: 99%
“…Estudios empíricos han existido varios y en diversos países, pero en su mayoría sobre el sector industrial y comercial. De todas formas sirven como punto de partida para este trabajo cuando identifican variables con notorio impacto en la rentabilidad, como el endeudamiento, el acceso al crédito, los niveles de inventario, la cantidad de personal ocupado, el peso salarial, el tamaño de los activos o el nivel de actividad ((Romero Espinosa et al, 2015); (Yardín, 2019); (Tong and Saladrigues, 2018); (Gschwandtner and Hirsch, 2018); (Melgarejo et al, 2014); (Laitinen, 2011)).…”
Section: Marco Teórico Y Antecedentesunclassified